Diabetes mellitus and abnormal glucose tolerance development after gestational diabetes: A three-year, prospective, randomized, clinical-based, Mediterranean lifestyle interventional study with parallel groups. Issue 4 (August 2015) - Pérez-Ferre, Natalia; Del Valle, Laura; Torrejón, Maria José; Barca, Idoya; Calvo, María Isabel; Matía, Pilar; Rubio, Miguel A.; Calle-Pascual, Alfonso L.
Summary Background & aims Women with prior gestational diabetes mellitus (GDM) have a high risk of developing type 2 diabetes mellitus (DM2) in later life. The study aim was to evaluate the efficacy of a lifestyle intervention for the prevention of glucose disorders (impaired fasting glucose, impaired glucose tolerance or DM2) in women with prior GDM. Methods A total of 260 women with prior GDM who presented with normal fasting plasma glucose at six to twelve weeks postpartum were randomized into two groups: a Mediterranean lifestyle intervention group (n = 130) who underwent an educational program on nutrition and a monitored physical activity program and a control group (n = 130) with a conventional follow-up. A total of 237 women completed the three-year follow-up (126 in the intervention group and 111 in the control group). Their glucose disorders rates, clinical and metabolic changes and rates of adherence to the Mediterranean lifestyle were analyzed. Results Less women in the intervention group (42.8%) developed glucose disorders at the end of the three-year follow-up period compared with the control group (56.75%), p < 0.05. The multivariate analysis indicated a reduction in the rate of glucose disorders with a BMI of less than 27 kg/m2 (OR 0.28; 0.12–0.65; p < 0.003), low fat intake pattern (OR 0.30; 0.13–0.70; p < 0.005), low saturated fat pattern (OR 0.30; 0.13–0.69; p < 0.005) and healthy fat pattern (OR 0.34; 0.12–0.94; p < 0.04). Conclusions Lifestyle intervention was effective for the prevention of glucose disorders in women with prior GDM. Body weight gain and an unhealthy fat intake pattern were found to be the most predictive factors for the development of glucose disorders. Current Controlled trials: ISRCTN24165302. http://www.controlled-trials.com/isrctn/pf/24165302.